Cardiac Slc25a49‐Mediated Energy Reprogramming Governs Doxorubicin‐Induced Cardiomyopathy through the G6P–AP‐1–Sln Axis - Sitong Wan; Jingyi Qi; Yi Xia; Chang Fan; Teng Xu; Xu Zhang; Jiaxin Shi; Chenxuan Wang; Yitong Cheng; Dongyuan Zhang; Rong Liu; Yinhua Zhu; et al. (Advanced Science)
Abstract Doxorubicin (Dox), a potent antitumor drug, is linked to cardiac toxicity. Few mechanism‐based therapies against cardiotoxicity are available. Dysfunction in mitochondrial energy metabolism contributes to Dox‐induced cardiomyopathy. It is aimed at exploring the association between specific mechanism of energy reprogramming and Dox‐induced cardiomyopathy. Cardiac‐specific ablation of Slc25a49 mice are generated by crossing Slc25a49flox/flox mice with Myh6‐Cre mice. Slc25a49HKO mice or SLC25A49KD cardiomyocytes is treated with Dox. Echocardiography, histological analysis, transmission electron microscopy, bulk RNA sequencing, cell bioenergetic profiling, metabolomics test, chromatin immunoprecipitation, and dual‐luciferase reporter assay are conducted to delineate the phenotype and elucidate the molecular mechanisms. Specific ablation of Slc25a49 in cardiomyocytes leads to exacerbated Dox‐induced cardiomyopathy, characterized by compromised mitochondrial respiration enhanced glycolysis and increased glycolytic metabolite glucose‐6‐phosphate (G6P) levels, subsequently activating the activator protein‐1 (AP‐1) complex. The stimulation of the G6P–AP‐1 axis intensifies myocardial damage via transcriptionally regulating Sarcolipin (Sln) expression. Strikingly, targeting of this axis with the AP‐1 inhibitor T‐5224 effectively improves survival and enhances cardiac function in Dox‐induced cardiomyopathy. This study provides mechanistic insights into energy reprogramming that permits myocardial dysfunction, and thus provides a proof of concept for antienergy reprogramming therapy for Dox‐induced cardiomyopathy through directly modulating G6P–AP‐1–Sln axis.